2021
DOI: 10.1021/jasms.0c00415
|View full text |Cite
|
Sign up to set email alerts
|

New Peak Detection Performance Metrics from the MAM Consortium Interlaboratory Study

Abstract: The Multi-Attribute Method (MAM) Consortium was initially formed as a venue to harmonize best practices, share experiences, and generate innovative methodologies to facilitate widespread integration of the MAM platform, which is an emerging ultra-high-performance liquid chromatography–mass spectrometry application. Successful implementation of MAM as a purity-indicating assay requires new peak detection (NPD) of potential process- and/or product-related impurities. The NPD interlaboratory study described herei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 30 publications
3
35
0
Order By: Relevance
“…The method has since been adopted in QC to release testing and MAM consortium has been formed to harmonize best practices and generate methodologies in the facilitation of the widespread integration of the MAM platform in QC labs ( Millán-Martín et al, 2020 ). Recently, industry-wide inter-laboratory study (28 participating labs) using pre-digested samples of the NISTmAb RM 8671 and pre-defined experimental protocol has been conducted to test the robustness of MAM methods ( Mouchahoir et al, 2021 ) ( Supplementary Table S7 ). A version of the methods suitable for process development has been successfully implemented in three Sanofi sites with automatization of sample preparation as well as data interpretation ( Song et al, 2021 ).…”
Section: Global Landscape On Biosimilar Approvalsmentioning
confidence: 99%
“…The method has since been adopted in QC to release testing and MAM consortium has been formed to harmonize best practices and generate methodologies in the facilitation of the widespread integration of the MAM platform in QC labs ( Millán-Martín et al, 2020 ). Recently, industry-wide inter-laboratory study (28 participating labs) using pre-digested samples of the NISTmAb RM 8671 and pre-defined experimental protocol has been conducted to test the robustness of MAM methods ( Mouchahoir et al, 2021 ) ( Supplementary Table S7 ). A version of the methods suitable for process development has been successfully implemented in three Sanofi sites with automatization of sample preparation as well as data interpretation ( Song et al, 2021 ).…”
Section: Global Landscape On Biosimilar Approvalsmentioning
confidence: 99%
“…This series of reports provided a useful baseline to identify measurements for which method advancement and regulatory assimilation would benefit from additional technology development and interlaboratory studies. Highly focused interlaboratory studies have since been reported by NIST and independent communities to harmonize best practices, deepen community consensus on method performance, and document a baseline performance upon which future method evolution may be based ( DeLeoz et al, 2017 ; Hudgens et al, 2019a ; Brinson et al, 2019 ; Coffman et al, 2020 ; Srzentić et al, 2020 ; Mouchahoir et al, 2021 ). A number of those interlaboratory studies are reviewed here, with the intention to spur future partnerships to target additional assays and/or method evolution through well-planned interlaboratory studies.…”
Section: Introductionmentioning
confidence: 99%
“…(B) Corresponding dates and key milestones for each NISTmAb interlaboratory study (MAM, glycosylation, NMR HOS, and HDX-MS). a MAM New Peak Detection Publication ( Mouchahoir et al, 2021 ). b MAM Attribute Analytics Publication (In progress).…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, specific setting for new peak detection were used to look for species ≥ 0.1% of the TIC signal and that had a 5× fold change, in line with parameters previously. 18 No new peaks were observed between the six manual preparations prepared by two analysts and the three automated preparations performed on the Hamilton 1 system. These data demonstrate the ability of the automation to reliably reproduce the manual sample preparation.…”
Section: Resultsmentioning
confidence: 94%